Reinforcing the learning of reinforced concrete design online / Chiew Fei Ha, Ong Mooi Lian and Lee Beng Yong - Chew, Fei Ha; Ong, Mooi Lian; Lee, Beng Yong (Universiti Teknologi MARA, Perlis, 2011)
Reinforced concrete design is a core subject in the civil engineering programme. Students are taught calculations for a safe design of reinforced concrete elements in accordance to the code of practice. The long and tedious calculations often restrict the number of examples that can be demonstrated in the limited classroom time. When practicing on their own, students do not have the means to verify their work in order to identify their mistakes. As such, exploiting the flexibility and convenience of the Internet, a web-based reinforced concrete design system is developed. It aims to provide students the opportunity to go through the design procedure at their own pace and convenience, and verifying worked solutions when doing practice questions. The web-based system is able to perform design calculations and display worked solution for beams, slabs, columns and footings. This system also generates proposed reinforcement for the elements, interwoven with explanation on the design procedure. A hands-on session has been carried out in order to seek feedback on the usability of the system from a group of students.